2009
DOI: 10.5894/rgci117
|View full text |Cite
|
Sign up to set email alerts
|

Condições Ambientais em Áreas Urbanas da Bacia Hidrográfica do Rio Caeté – Amazônia Oriental - Brasil

Abstract: A Bacia Hidrográfica do Rio Caeté possui 2.195km 2 de área e extensão do rio principal e, aproximadamente, 149km das nascentes (município de Bonito) à foz (municípios de Bragança e Augusto Corrêa). O Caeté drena sete municípios (Bonito, Tracuateua, Ourém, Capanema, Santa Luzia do Pará, Bragança e Augusto Corrêa), entretanto os estudos foram realizados nos municípios de Bragança e Santa Luzia do Pará por serem as áreas mais urbanizadas da bacia. O objetivo deste trabalho foi determinar os principais problemas a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
14

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 1 publication
0
12
0
14
Order By: Relevance
“…Cei (2010) reported that the incidence of diseases in coastal communities caused by environmental problems has exhausted the productive capacity of the ecosystems. Similar problems have been found in many other riverside communities in the Amazon region (Gorayeb, 2009;Guimarães et al, 2009aGuimarães et al, , 2009bSimonian et al 2010;Pereira et al, 2007Pereira et al, , 2010Silva et al, 2011, as well as in other countries with similar socio-economic conditions, such as China, Mexico and Chile. In most cases, efforts have been made to guarantee both the development of rural/urban areas and the adequate use of local natural resources (Xue et al, 2004;Sánchez-Gil et al, 2004;Alvial and Recule, 1999).…”
Section: Discussionmentioning
confidence: 61%
“…Cei (2010) reported that the incidence of diseases in coastal communities caused by environmental problems has exhausted the productive capacity of the ecosystems. Similar problems have been found in many other riverside communities in the Amazon region (Gorayeb, 2009;Guimarães et al, 2009aGuimarães et al, , 2009bSimonian et al 2010;Pereira et al, 2007Pereira et al, , 2010Silva et al, 2011, as well as in other countries with similar socio-economic conditions, such as China, Mexico and Chile. In most cases, efforts have been made to guarantee both the development of rural/urban areas and the adequate use of local natural resources (Xue et al, 2004;Sánchez-Gil et al, 2004;Alvial and Recule, 1999).…”
Section: Discussionmentioning
confidence: 61%
“…Contudo, as águas dos rios da região Amazônica possuem valores de pH ácidos (SIOLI, 1991). Gorayeb (2008), ao longo do rio Caeté, detectou valores de pH entre 5 e 6, típicos dos rios da região Amazônica.…”
Section: Methodsunclassified
“…Alguns autores (ARAÚJO, 2008;BARCELLOS et al, 2005;CORREIA, 2004;COSTA et al, 2006;GORAYEB et al, 2009;GUARIM, 2005;LACERDA et al, 2006;MOCHEL et al, 1991;MOCHEL, 1995;MOCHEL et al, 2001;MOCHEL, 2002;MORA-ES, 2008;MOTTA, 1996;OLIVEIRA, 2006;SILVA et al, 2009;ESPIG;REIS;ARAÚJO, 2007) relatam que os processos de urbanização em zonas costeiras representam um dos maiores desafi os para a gestão ambiental do país, uma vez que neste espaço convergem os principais vetores de fl uxos de toda ordem, compondo um amplo e complexo mosaico de tipos e padrões de ocupação humana, de uso do solo e dos recursos naturais e de exploração econômica em geral.…”
Section: Introductionunclassified